Shifts In Bilingual Book “Mengapa Bali disebut Pulau Seribu Pura”: Systemic Functional Linguistics - Dewi Putriani Yogosara Lodewijk; I Ketut Suardana; Komang Astiari (Focus Journal : Language Review, 2025)
Translation is process of transferring messages from the source language into the target language. The process of transferring message from the source language needs certain strategy. Shifts can be avoided occurring in translation to achieve equivalence between the source language and the target language. This research would like to explore the level of equivalence by getting shifts from the source language into the target language in the book entitled “Mengapa Bali Disebut Pulau Seribu Pura”. The book is written in two languages, English serves as the source language, while Indonesia serves as the target language. The clauses used in the source language gets shift in the equivalence in the target language. Therefore, the shifts explored in the translation are argument shifts involving; participant, process, and circumstance. The theory used to explore shifts found in the target language is Systemic Functional Linguistics theory especially ideational function. This research uses qualitative approach, grounded theory, namely to improve theory of SFL in translation field. The data used for this research were clauses getting shifts in the book such as; participant, process, and circumstance. The result of this research is presented in description supporting with the tables of the source and the target languages. The tables involve the arguments in the clauses getting shifts. The tables are supported by the description. the result of this research shows that the shifts occur in the participant, process, and circumstance. The shifts occurring in participants indicate that shifts in functions of participant since the function of participant is influenced by shifts in the process. The shifts occurring in process indicate the absence of modality and shifts in type of activities. The shifts occurring in circumstance indicate shifts in tense so the meaning of the text become far equivalence. This research is categorised as applied linguistics research so this research has significance for; translation studies, Systemic Functional Linguistics, semiotic, and teaching. This research is expected to add linguistics library so this research can be used as reference for the following translation research. This research is expected to be able to trigger other translation and Systemic Functional Linguistics researchers so the translation and Systemic Functional fields become more popular in the study. In addition, the research is expected to give some knowledge for the communities that translation is not the same word, but the shifts can occur which cause far equivalence.